Character Building through Local Cultural Values Tradition of Jolenan in a Village Community of Purworejo, Indonesia - Tarto Tarto; Bambang Susanto; Victor Novianto (UM Purwokerto Press, 2023)
This research is intended to explicate the formation of the character of the village community through the values of the local cultural wisdom (tradition) of Jolenan and describe those characters that formed through the local cultural values of the tradition of Jolenan, and to elucidate the process of inculcating local cultural values of the Jolenan tradition. This study took place in Somongari Village, Purworejo, Central Java, Indonesia. The data were collected through interviews, observation, and documentation. The validity of the data is obtained through triangulation. Miles and Huberman’s interactive method was applied to analyze the data. The results of this study postulate that: (1) the tradition of Jolenan comprises local cultural values such as religious, entertainment, economical, communal work, manners, togetherness, harmony, unity, bravery, education, and environmental awareness. (2) The characters which are formed through the tradition of Jolenan include religious, honesty, responsibility, discipline, hard-working, politeness, communal work, patriotism, self-reliance, democratic. (3) The values of Jolenan were inculcated through an educational institution, family, religious, economic, and political aspects. In addition, the establishment of the tradition of Jolenan also touched tourism and social aspects.